Crimean-Congo hemorrhagic fever virus: Genetic analysis and tick survey in Turkey - Tonbak, Sukru; Aktas, Munir; Altay, Kursat; Azkur, Ahmet K.; Kalkan, Ahmet; Bolat, Yusuf; Ozdarendeli, Aykut (Amer Soc Microbiology, 2006)
Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne virus in the family Bunyaviridae, genus Nairovirus. The virus is transmitted to humans through infected tick bites or from direct contact with viremic animals or humans. In the present study, a total of 1,015 adult ticks were collected from cattle (603 specimens), sheep (17 specimens), and goats (395 specimens) in the Kelkit Valley in Turkey. Four tick species were recognized on the animals in the surveyed region. The most abundant species were Rhipicephalus bursa and Hyalomma marginatum marginatum, at 47.68% (484/1,015) and 46.40% (471/1,015), respectively. Reverse transcriptase PCR was used to recover partial sequences of the CCHFV small (S) genome segment. The presence of CCHFV was determined in 3 of 33 (9.09%) R. bursa pools and in 1 of 31 (3.22%) H. m. marginatum pools. Virus sequences from R. bursa were extremely different from those of the Greek CCHFV strain (U04958) isolated from an R. bursa tick. Phylogenetic analysis indicated that the CCHFV isolates obtained in this study clustered in group 5, whose range encompasses southwestern Russian and Kosovo. This is the first evidence of CCHFV in ticks from Turkey. Even though Hyalomma is the main vector for CCHFV, R. bursa may play a role in CCHFV transmission.
Keywords: Theileria; Outbreak; Cattle